Influence of breastfeeding on quality of life and serum IgE level in allergic rhinitis children (Bangladesh Journal of Medical Science, 2017)
Background: Allergic rhinitis is a known health problem worldwide.Objective: The aim of the study was to determine the association between breastfeeding and serum IgE level as well as its impact on quality of life in children with allergic rhinitis.Methodology: A cross sectional comparative study was done among pediatric patients aged 6-12 who have allergic rhinitis with evidence of positive skin prick test (SPT), for 30 specifically selected patients each for breastfed and non-breast-fed. For each patient, serum IgE was taken and interviewed using the modified allergy questionnaire by validated Sher Allergy Specialists questionnaire (Florida) and Rhinoconjuntivitis Quality of Life Questionnaires (RQLQ) by Juniper. Statistical analysis was performed using SPSS 13.0. The significant association was analyzed using Pearsons chi-square and Mann-Whitney U tests.Results: There was no significant difference (p = 0.688) with regards to serum IgE level between breastfed and non-breast-fed children. However, children who were breastfed have a better mean of quality of life (mean=1.1679) than non-breast-fed (mean=1.5274).Conclusion: Our study showed that there is no association between breastfeeding and serum IgE level. Nevertheless, the quality of life is better in breastfed children. A larger sample and longer duration of study are required to substantiate these findings.Bangladesh Journal of Medical Science Vol.16(4) 2017 p.530-534